Low Cost System for Partial Discharge Monitoring in Power Transformers by Piezoelectric Sensors - Castro, B. A. [UNESP]; Clerice, G. A. M. [UNESP]; Andreoli, A. L. [UNESP]; Campos, F. S. [UNESP]; Ulson, J. A. C. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
Partial discharge damages in power transformers require high cost monitoring procedures based on corrective maintenance or even interruptions of the power system. The development of online non-invasive monitoring systems to detect partial discharges in power transformers has great relevance since it can reduce significant maintenance costs. Some critical factors in the operation of transformers such as overload, nonlinear loads, transient voltage surges by atmospheric origin and switching, can make the insulation system of transformers to lose their physical and chemical properties. Therefore, these operating conditions can cause early deterioration of the insulation, causing internal partial discharges that may develop into major defects and thus shorten the useful life of electrical equipment. This research aimed to apply a low cost piezoelectric sensors (PZTs) for partial discharge identification in power transformers and a study was conducted on the obtained a good results for identification with PZTs.
Keywords: Partial Discharge; Acoustic Emission; Piezoelectric Sensors; Mitigation